Do exclusionary rules ensure a fair trial?: a comparative perspective on evidentiary rules - Gless, Sabine; Richter, Thomas (Ius Gentium, 2019)
Part I: Comparative Perspectives -- Chapter 1. The Potential to Secure a Fair Trial Through Evidence Exclusion: A Swiss Perspective -- Chapter 2. The Potential to Secure a Fair Trial Through Evidence Exclusion: A German Perspective -- Chapter 3. Regulating Interrogations and Excluding Confessions in the United States: Balancing Individual Rights and the Search for the Truth -- Chapter 4. The Potential to Secure a Fair Trial Through Evidence Exclusion: A Taiwanese Perspective -- Chapter 5. The Potential to Secure a Fair Trial Through Evidence Exclusion: A Chinese Perspective -- Chapter 6. Criminal Justice and the Exclusion of Incriminating Statements in Singapore -- Part II: Exclusionary Rules – quo vadis -- Chapter 7. The Purposes and Functions of Exclusionary Rules: A Comparative Overview -- Chapter 8. The Fair Trial Rationale for Excluding Wrongfully Obtained Evidence -- Chapter 9. Exclusionary Rule of Illegal Evidence in China: Observation from Historical and Empirical Perspectives -- Chapter 10. Securing a Fair Trial Through Exclusionary Rules: Do Theory and Practice form a Well-balanced Whole? -- Chapter 11. Exclusionary Rules – Is It Time for Change?